The evolution of phases in FeNiCoCrCuBx high entropy alloys produced through microwave sintering and vacuum arc melting - İrem B. Algan Şimşek; Sükrü Talaş; Adem Kurt (Revista de Metalurgia, 2022)
Microwave heating and sintering techniques are applied to various production lines and material systems to improved their microstructure and mechanical properties in comparison to conventional means of production. These techniques also consume less power and energy compared to conventional heating methods. In this study, the production of high entropy alloys (HEA) by arc melting was carried out with specimens made from compacted and sintered elemental powders; the sintering process of alloy powders prior to remelting prevents certain problems such as porosity and uneven mixing that may occur during casting. We investigated the effects of conventional and microwave sintering processes prior to remelting and casting on structure and properties of FeNiCoCrCuBx HEA. Our results show that microwave sintering changes the size and shape of phases and microstructure of the alloy by affecting the liquid-phase separation mechanism. Three-point bending strength and ductility of alloys produced by microwave sintering were superior to conventional sintering.